2022
DOI: 10.2196/27534
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Visualization Applications in Population Health and Health Services Research: Systematic Scoping Review

Abstract: Background Simple visualizations in health research data, such as scatter plots, heat maps, and bar charts, typically present relationships between 2 variables. Interactive visualization methods allow for multiple related facets such as numerous risk factors to be studied simultaneously, leading to data insights through exploring trends and patterns from complex big health care data. The technique presents a powerful tool that can be used in combination with statistical analysis for knowledge disco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…The tool is designed to streamline the preliminary examination of complex spatiotemporal datasets, making it easier to navigate data that would be otherwise difficult to visualize at scale. There’s a rising awareness among health researchers about the importance of interactive tools that offer straightforward visualizations for intricate datasets 31 , 32 —EpiVECS is designed with this necessity in mind.…”
Section: Discussionmentioning
confidence: 99%
“…The tool is designed to streamline the preliminary examination of complex spatiotemporal datasets, making it easier to navigate data that would be otherwise difficult to visualize at scale. There’s a rising awareness among health researchers about the importance of interactive tools that offer straightforward visualizations for intricate datasets 31 , 32 —EpiVECS is designed with this necessity in mind.…”
Section: Discussionmentioning
confidence: 99%
“…Only two reviews in our sample used interactive data visualisation, and one of these was an example of systematic evidence mapping from the environmental health field rather than a scoping review (in environmental health, systematic evidence mapping explicitly involves producing a searchable database [ 35 ]). A scoping review of papers on the use of interactive data visualisation in population health or health services research found a range of examples but still limited use overall [ 13 ]. For example, the authors noted the currently underdeveloped potential for using interactive visualisation in research on health inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers without the relevant programming skills can now use several online platforms (such as Tableau [ 11 ] and Flourish [ 12 ]) to create interactive data visualisations. The benefits of using interactive visualisation in research include the ability to easily present more than two variables [ 13 ] and increased engagement of users [ 14 ]. Unlike static graphs, interactive visualisations can allow users to view hierarchical data at different levels, exploring both the “big picture” and looking in more detail ([ 15 ], p. 291).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HGraph shows a static overview of a person's health, being able to track the trajectory of different parameters, how fast they change, and how they respond to events such as medical care actions and interventions [9]. With the advances in digital medicine [10], data visualization has been used as an important tool for gaining insight into healthcare datasets, in addition to the electronic health records that are increasingly replacing paper records in hospitals and clinics around the world.…”
Section: Related Jobsmentioning
confidence: 99%